Genotypic Detection of Some Virulence Factors Among Aeromonas hydrophila Isolated from Diarrhea Cases (Iraq) - Ilham A. Bunyan (Journal of Pure and Applied Microbiology, 2018)
The present study included the detection of some virulence factors of Aeromonas hydrophila under molecular level to clinical isolates were taken from patients suffering from diarrhea during the period from July (2017) to October (2017). Molecular detection of Hemolysin gene (ahh) was done for all isolates. The results showed that all isolates (100%) gave positive results for this virulence gene. the positive results were detected by the presence of (130) bp bands when compared with allelic ladder. The genomic DNA of the samples was extracted and bands were observed by performing agarose gel electrophoresis. When PCR was performed, results clearly indicate that all isolated organisms contained serine protease gene and all the amplified products produced a band at the level of (900 bp) when compared with the allelic ladder. Molecular detection of this gene was carried out by using a specific PCR primer were done by comparison with allelic ladder which gave a (309bp) It was found that (Aerolysin) gene present in (12)(75%) of the positive samples. Lip gene was also detected in A. hydrophila samples and found that all 16 samples (100%) gave positive results to this gene which gave molecular length (382) bp. Molecular study was carried out to show the sequence identity of cytotonic enterotoxins gene in Aeromonas spp. to that in A. hydrophila. Analysis of the A. hydrophila genome revealed a number of a putative virulence factors, including a gene that heat-labile cytotonic enterotoxin (alt). Our study showed that all (16) isolates (100%) gave positive results to this gene, which gave molecular length (442)bp. Molecular detection of cytotonic enterotoxins gene (ast) was done for (16) A. hydrophila isolates and the results showed that all isolates have this gene (100%). The positive results for (ast) virulence were detected by the presence of (331) bp band compared with allelic ladder.